Efektivitas Menonton Video Kartun terhadap Tingkat Nyeri Selama Prosedur Invasif pada Anak Sekolah - Rini Wahyuni Mohamad; Nani Nurhaeni; Dessie Wanda (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the effectiveness of watching cartoon videos on pain levels in school children during invasive procedures. The method used is a systematic review by searching for articles on the Scopus, ProQuest, EBSCOhost, ScienceDirect, Embase, ClinicalKey, Wiley Online and Google Scholar databases. The results showed that there were several themes obtained from the results of the literature study, including: 1) giving distraction techniques to watch animated cartoons to reduce pain levels; 2) the effect of audiovisual distraction therapy during invasive procedures; 3) the benefits of distraction techniques; 4) the level of pain in children. In conclusion, the distraction technique of watching cartoon videos is effective in reducing pain during invasive procedures in school children. Keywords: School Children, Watching Cartoon Video Therapy, Pain Level